Speech and language therapists’ views about AAC system acceptance by people with acquired communication disorders - Pampoulou, Eliada (My University, 2018)
Objective: Some adults with acquired communication disorders are faced with an inability to communicate coherently through verbal speech with their communication partners. Despite the fact that a variety of augmentative and alternative communication (AAC) aided systems is available to assist them in communicating, not all adults accept them. In Cyprus, there is scant research focusing on the factors that are linked to AAC system acceptance and abandonment. Methods: To address this gap, this research involves exploring the experiences of six speech and language therapists supporting adults with acquired communication disorders, who could benefit from the use of AAC systems. The main research question is: What are the factors that influence AAC system acceptance or abandonment? The method used for data collection, was semi-structured interviews and the transcripts were analyzed thematically. Results: The findings show that a number of factors influence the acceptance of AAC systems. These include the time since onset and acceptance of disability, the person’s attitude towards communication facilitators, and the perceptions about AAC systems. These findings indicate that the process of accepting an AAC system is multi-layered and these layers are interrelated. Conclusions: More research is warranted focusing directly on the experiences of people with acquired communication disorders and their communication partners.Implications for RehabilitationThe different myths about AAC systems need to be challenged such that awareness about their usefulness is raised.AAC specialists need to find ways to spread the message that AAC systems can actually support language, speech and communication through different dissemination avenues, such as articles in newspapers and talks through the media.
Keywords: Abandonment; Acceptance; Acquired communication disorders; Augmentative and alternative communication; Technology